PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SABUN CAIR MERK LUX DI TRANSMART CEMPAKA PUTIH - Ratna Mintarsih; Boma Jonaldy Tanjung (Bajang Institute, 2024)
This research aims to determine how much influence brand image has on puchasing decision for Lux Body wash at Transmart Cempaka Putih, partially and simultaneously. Currently there is a problem related to the boycott of products that This research uses quantitative methods. The sampling technique used observation and a questionnaire with a Likert scale and 40 respondents were obtained by processing the data using SPSS version 20 software The research method used was descriptive analysis method, validity test, classic assumption test which includes normality test and simple linear regression test. Hypothesis testing includes partial regression tests (t tests), simultaneous regression tests (f tests) and coefficient of determination tests using SPSS version 20 software. The results of research using partial regression (t tests) show that Brand Image has no significant effect on Purchasing Decisions, this is shown by the results of the calculated t data (0.1396) < t table (1.6859) and shows a significant value of 0.171 > probability 0.05. Simultaneous research results (f test) show that Brand Image has no influence on Purchasing Decision, this is shown by the results of calculated f data (1.948) < f table (4.18) and the significant value (0.171) > 0.05 significant level. Then an R Square value of (0.008) was obtained which shows that the dependent variable Purchase Decision can be explained by the independent variable Brand Image 0.8% while the remaining 99.2% is influenced by other factors not explained in the research